PERSONALIZED POINT-OF-SALE (POS) AND KITCHEN DISPLAY SYSTEM (KDS) WITH QR CODE ORDERING FOR RESTORAN NURHIKMAH - Adam, Fabian (Project Report (BSc.) -- Universiti Malaysia Sarawak, 2023., 2023)
Restoran Nurhikmah was a "mamak" restaurant located in Lutong, Miri and was owned by Mr. Abdul Azeez. Over the 20 years that the business had been running, the restaurant did not have a POS system to manage orders and sales, relying on conventional methods instead. This led to inefficient and unproductive management of the business. To solve the mentioned problems, a system consisting of a Point-of-Sale (POS) system, a Kitchen Display System (KDS), and a QR code ordering system was proposed and developed in the project. The aim was to increase the overall efficiency and productivity of the business. A Gantt Chart of the whole project was provided in the report, and the Rapid Application Development (RAD) methodology was utilized to complete the project scopes within the given timeline. A comparison of the proposed system with existing systems in the market and the software requirements of the project was discussed in the report. The software used, the challenges faced during the development process, and the end product of the development were provided in the report. During the testing phase, the results were analyzed, and achievements, limitations, and constraints of the new system were outlined. The report also addressed future works that could be undertaken to further enhance the system's capabilities.